2005
DOI: 10.1128/aac.49.3.1029-1038.2005
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP (3′-5′-Cyclic Diguanylic Acid) Inhibits Staphylococcus aureus Cell-Cell Interactions and Biofilm Formation

Abstract: Staphylococcus aureus is an important pathogen of humans and animals, and antibiotic resistance is a public health concern. Biofilm formation is essential in virulence and pathogenesis, and the ability to resist antibiotic treatment results in difficult-to-treat and persistent infections. As such, novel antimicrobial approaches are of great interest to the scientific, medical, and agriculture communities. We recently proposed that modulating levels of the cyclic dinucleotide signaling molecule, c-di-GMP (cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 70 publications
(61 reference statements)
4
103
0
3
Order By: Relevance
“…The data presented in the current study show that bacterial c-di-GMP is an immunostimulatory molecule and we have previously demonstrated that c-di-GMP can inhibit bacterial infection (19,21) and has potential in cancer treatment (20). Due to its microbial origin and its effect on the host response, c-di-GMP can be considered as a danger signal or novel pathogen-associated molecular pattern.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The data presented in the current study show that bacterial c-di-GMP is an immunostimulatory molecule and we have previously demonstrated that c-di-GMP can inhibit bacterial infection (19,21) and has potential in cancer treatment (20). Due to its microbial origin and its effect on the host response, c-di-GMP can be considered as a danger signal or novel pathogen-associated molecular pattern.…”
Section: Discussionmentioning
confidence: 56%
“…2 shows that pretreatment with c-di-GMP 12 and 6 h before bacterial challenge produces a significant prophylactic effect with a 1.5 and 3.8 log (ϳ10,000-fold) reduction of the mean bacterial CFU in tissues using a 50-and 200-nmol dose, respectively, compared with the untreated control ( p Ͻ 0.05 and p Ͻ 0.001, respectively). Had c-di-GMP only inhibited biofilm formation, as previously shown in our in vitro (19) and in vivo models (21), we would not have expected to find such dramatically reduced numbers of bacterial cells between pretreated and nontreated mice. These results suggest that c-di-GMP might stimulate the innate immune response.…”
Section: Prophylactic Pretreatment Of Mice With C-di-gmp Inhibits Infmentioning
confidence: 52%
See 2 more Smart Citations
“…In studies of biofilm-reducing compounds, approximate 40% to 80% reductions in biofilm mass were observed [25,27]. With six concentrations of C2DA studied, given the approximate 20% standard deviation (SD), we could detect a difference of 75% of control values with 80% power using ANOVA analysis with three wells for the biofilm inhibition studies.…”
Section: Methodsmentioning
confidence: 97%